Sm-Fe-based permanent magnet film and preparation method and application thereof
By using the laminated structure of Sm-Fe-based materials and annealing heat treatment technology in the magnetic film, the problem of the orientation plane of the easy magnetization direction in the magnetic film is solved, and a Sm-Fe-based permanent magnet film with high magnetic anisotropy and coercivity is prepared, which is applied to microelectromechanical systems, microelectronic systems, magnetic recording materials and spintronic devices.
Patent Information
- Application Number
- CN202510181941.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-18
AI Technical Summary
In magnetic films, the direction of easy magnetization is often preferentially oriented in the plane, making it difficult to obtain a thin film with perpendicular magnetic anisotropy, which seriously limits the development of high-performance functional devices.
Using Sm-Fe-based material, a Sm-Fe-based permanent magnet film with magnetic perpendicular anisotropy was prepared by depositing a Ta buffer layer, a Sm-Fe-based layer and a Ta cover layer sequentially on the substrate and performing annealing heat treatment.
Excellent magnetic anisotropy in the vertical direction is achieved, with significantly higher coercivity, reaching 2427Oe, exceeding the 650Oe of films close to SmFe2 components reported in the literature.
Smart Images

Figure CN119811823A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a permanent magnetic film, in particular to a Sm-Fe based permanent magnetic film and a preparation method and application thereof, belonging to the technical field of permanent magnetic films. Background Art
[0002] Magnetic anisotropy is a key property of magnetic materials, and perpendicular anisotropy plays an important role in various applications, such as spintronic devices, microelectromechanical systems, magnetic nanosensors, magnetic storage, and magnetic recording. In magnetic films, the easy magnetization direction is often preferentially oriented in the plane, so it is difficult to obtain films with perpendicular magnetic anisotropy, which seriously limits the development of high-performance functional devices. Epitaxial growth is an effective method for manufacturing films with perpendicular anisotropy. However, the perpendicular anisotropy of epitaxially grown films is affected by many factors, such as growth conditions, crystal structure, lattice matching, and film thickness, and there are still many difficulties in preparation. Summary of the invention
[0003] The main purpose of the present invention is to provide a Sm-Fe based permanent magnetic film and a preparation method thereof, so as to overcome the deficiencies in the prior art.
[0004] Another object of the present invention is to provide an application of the Sm-Fe based permanent magnetic film.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] The embodiment of the present invention provides a Sm-Fe-based permanent magnetic film, which includes a Ta buffer layer, a Sm-Fe layer and a Ta cap layer stacked in sequence along the thickness direction of the substrate, wherein the Sm-Fe layer has a perpendicular magnetic anisotropy, and the Sm-Fe layer includes pure SmFe x Phase polycrystalline film, x=1.8~2.
[0007] The embodiment of the present invention further provides a method for preparing a Sm-Fe based permanent magnetic film, which comprises:
[0008] A Ta buffer layer, a Sm-Fe layer and a Ta capping layer are sequentially deposited on a substrate by magnetron sputtering technology, and then the obtained composite film is subjected to annealing heat treatment to obtain a Sm-Fe-based permanent magnetic film.
[0009] The embodiment of the present invention also provides the application of the Sm-Fe based permanent magnetic film in a microelectronic system, a micro-electromechanical system, a magnetic recording material or a spin electronic device.
[0010] Compared with the prior art, the present invention has at least the following beneficial effects:
[0011] The Sm-Fe-based permanent magnetic film provided by the present invention has a high degree of perpendicular anisotropy, exhibits excellent magnetic anisotropy in the perpendicular direction, and has a significantly higher coercive force of 2427Oe, which exceeds the 650Oe of a film with a composition close to SmFe2 reported in the literature. The successful preparation of the magnetic film with good perpendicular anisotropy has important application value in the application of micro-electromechanical systems, microelectronic systems, magnetic recording materials and spin electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0013] Figure 1 Schematic diagram of the structure of a Sm-Fe based permanent magnetic film provided by a typical embodiment of the present invention;
[0014] Figure 2a The XRD spectrum of a Sm-Fe based permanent magnetic film prepared by depositing a SmFex (x=1.5-9) layer at 300°C, depositing a 50nm Ta capping layer, and annealing at 700°C for 0.5h in a typical embodiment of the present invention;
[0015] Figure 2b The XRD spectrum of a Sm-Fe based permanent magnetic film obtained by depositing a SmFe2 layer at different temperatures (250°C to 700°C) and then depositing a 50nm Ta capping layer and annealing at 700°C for 0.5h in a typical embodiment of the present invention;
[0016] Figure 2c The XRD spectrum of a Sm-Fe based permanent magnetic film prepared by depositing a 50-100 nm Ta capping layer after depositing a SmFe2 layer at 300° C. and annealing at 700° C. for different times (15 minutes to 1 hour) in a typical embodiment of the present invention;
[0017] Figure 2d In a typical embodiment of the present invention, SmFe is deposited at 500°C. 1.9 XRD pattern of Sm-Fe based permanent magnetic film prepared by depositing a 50nm Ta capping layer and annealing at 700℃ for 1h;
[0018] Figure 3 SmFe prepared in Comparative Example 1 0.5 SmFe based permanent magnetic film 0.5Magnetic hysteresis loops of (500℃) / Ta(AA) thin film without annealing along the parallel ( / / ) and perpendicular (⊥) directions;
[0019] Figure 4 The hysteresis loop diagram of the sample of the SmFe-based permanent magnetic film SmFe(500℃) / Ta(AA) film prepared in Comparative Example 2 and annealed at 700℃ along the parallel ( / / ) and perpendicular directions (⊥);
[0020] Figure 5 The SmFe prepared in Example 1 of the present invention 1.9 SmFe based permanent magnetic film 1.9 Magnetic hysteresis loops of (500℃) / Ta(AA) thin films annealed at 700℃ along the parallel ( / / ) and perpendicular (⊥) directions;
[0021] Figure 6 The SmFe prepared in Example 2 of the present invention 1.9 Magnetostriction coefficient of (300℃ / 550℃) / Ta(BA) film after annealing at 700℃ for different times.
[0022] Description of the drawings: 1-Si(100) substrate, 2-Ta buffer layer, 3-Sm-Fe layer, 4-Ta capping layer. DETAILED DESCRIPTION
[0023] In order to solve the problem that in magnetic films, the easy magnetization direction is often preferentially oriented in the plane, making it difficult to obtain a film with perpendicular magnetic anisotropy, which seriously limits the development of high-performance functional devices, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice, providing a Sm-Fe-based permanent magnetic film with perpendicular anisotropy and a preparation method thereof.
[0024] Sm-Fe material is a special alloy material, belonging to the Laves phase compound. Sm-Fe material has a high negative magnetostriction coefficient, which means that the material will change in volume under the action of a magnetic field. This property is mainly due to the high magnetoelastic energy of Sm ions and the large exchange constant of the intermetallic compound composed of rare earth and iron. These characteristics enable Sm-Fe material to maintain a high magnetostriction coefficient at room temperature, especially along the easy magnetization axis
[111] direction, and its magnetostriction coefficient can reach -2010ppm.
[0025] The Sm-Fe based permanent magnetic film of the present invention has good magnetostrictive properties. Since the magnetostrictive properties of the Sm-Fe2 phase film are limited in a direction parallel to the substrate, but can be magnetostrictive in a direction perpendicular to the substrate, showing good magnetic properties, the Sm-Fe2 phase film shows excellent magnetic perpendicular anisotropy in a direction perpendicular to the substrate.
[0026] The technical solution, its implementation process and principle will be further explained as follows.
[0027] Specifically, as one aspect of the technical solution of the present invention, a Sm-Fe-based permanent magnetic film includes a Ta buffer layer, a Sm-Fe layer and a Ta cap layer stacked in sequence along the thickness direction of the substrate, wherein the Sm-Fe layer has a perpendicular magnetic anisotropy, and the Sm-Fe layer includes pure SmFe x Phase polycrystalline film, x = 1.8N2.
[0028] In some embodiments, the Sm-Fe layer preferably comprises pure SmFe 1.9 Phase polycrystalline film has a higher magnetostriction coefficient, so it produces higher stress under the magnetic field perpendicular to the film surface, showing obvious magnetic anisotropy, making SmFe 1.9 The magnetic properties of the film are much better than those of films with other compositions.
[0029] In some embodiments, the Sm—Fe layer has a thickness of 950 to 1050 nm.
[0030] In some embodiments, the substrate may include at least any one of a Si substrate, a Si / SiO2 substrate, an aluminum oxide substrate, etc., preferably a Si (100) substrate, but not limited thereto.
[0031] In some embodiments, the Ta buffer layer has a thickness of 50-100 nm.
[0032] In some embodiments, the thickness of the Ta capping layer is 50-100 nm. The Ta capping layer deposited by the present invention can effectively prevent the volatilization of Sm, and successfully synthesizes pure SmFe at a composition ratio of nearly 1:2. x Phase film.
[0033] In some embodiments, the Sm-Fe based permanent magnetic film has a thickness of 1050-1250 nm.
[0034] For details, please refer to Figure 1 As shown, the Sm-Fe based permanent magnetic film includes, from bottom to top, a Si (100) substrate 1, a Ta buffer layer 2, a Sm-Fe layer 3 and a Ta capping layer 4.
[0035] As another aspect of the technical solution of the present invention, a method for preparing a Sm-Fe based permanent magnetic film involves: using magnetron sputtering technology to deposit a Ta buffer layer, a Sm-Fe layer and a Ta covering layer on a substrate in sequence, and then annealing the obtained composite film to obtain a Sm-Fe based permanent magnetic film.
[0036] In some specific embodiments, the preparation method specifically includes: using magnetron sputtering technology, using an inert gas as a sputtering gas, and using a Ta target as a target material, sputtering and depositing a Ta buffer layer on the surface of the substrate; wherein the pressure of the inert gas used is 0.8 to 3 Pa, the sputtering power is 50 to 120 W, the sputtering time is 5 to 10 min, and the deposition temperature is 250 to 350 ° C.
[0037] In some specific embodiments, the preparation method specifically includes: using magnetron sputtering technology, using an inert gas as a sputtering gas, using a Fe target and a Sm target as target materials, and using a co-sputtering method to sputter and deposit on the surface of the Ta buffer layer to form a Sm-Fe layer; wherein the pressure of the inert gas used is 0.8 to 3 Pa, the sputtering power is 10 to 150 W, the sputtering time is 10 to 250 min, and the deposition temperature is 250 to 700 ° C, preferably 250 to 550 ° C.
[0038] In some specific embodiments, the preparation method specifically includes: using magnetron sputtering technology, using an inert gas as a sputtering gas, and using a Ta target as a target material, sputtering and depositing a Ta covering layer on the surface of the Sm-Fe layer; wherein the pressure of the inert gas used is 0.8 to 3 Pa, the sputtering power is 50 to 120 W, the sputtering time is 3 to 60 min, and the deposition temperature is 250 to 350 ° C.
[0039] In some specific embodiments, the preparation method may also include: before depositing the Ta buffer layer on the substrate, first using magnetron sputtering technology, using an inert gas as a sputtering gas, to bombard the surface of the substrate with ions; wherein the pressure of the inert gas used is 1 to 5 Pa, the sputtering power is 20 to 60 W, and the sputtering time is 10 to 40 min.
[0040] Furthermore, the aforementioned inert gas may be argon, but is not limited thereto.
[0041] In magnetic films, the easy magnetization direction is often preferentially oriented in the plane, so it is difficult to obtain a film with perpendicular magnetic anisotropy. The preparation method of the Sm-Fe based permanent magnetic film changes the phase formation behavior of the Sm-Fex film with the Fe composition ratio x and determines the formation of the main SmFe x The composition range of the phase was studied, and Sm-Fe films with different deposition temperatures were prepared. The optimal deposition temperature was found, and Sm-Fe films with excellent magnetic anisotropy were prepared. x Mutually.
[0042] In some more specific embodiments, the preparation method specifically comprises the following steps:
[0043] (1) using magnetron sputtering technology, with argon as the sputtering gas, to bombard the surface of the substrate with ions to obtain a substrate; in step (1), the pressure of the argon gas is 1 to 5 Pa, the RF sputtering power is 20 to 60 W, and the sputtering time is 10 to 40 min;
[0044] (2) using magnetron sputtering technology, with argon as the sputtering gas and a Ta target as the target material, to sputter and deposit a Ta buffer layer on the surface of the substrate; in step (2), the pressure of the argon gas is 0.8 to 3 Pa, the sputtering power is 50 to 120 W, and the sputtering time is 5 to 10 min;
[0045] (3) using magnetron sputtering technology, argon gas as the sputtering gas, and Fe target and Sm target as the target material; using a co-sputtering method, a Sm-Fe film (i.e., the aforementioned "Sm-Fe layer") is deposited on the Ta buffer layer; in step (3), the pressure of the argon gas is 0.8-3 Pa, the sputtering power is 10-150 W, and the sputtering time is 10-250 min;
[0046] (4) using magnetron sputtering technology, with argon as the sputtering gas and a Ta target as the target material, to deposit a Ta capping layer on the surface of the Sm-Fe layer; in step (4), the pressure of the argon gas is 0.8 to 3 Pa, the sputtering power is 50 to 120 W, and the sputtering time is 3 to 60 min;
[0047] (5) The Sm-Fe based permanent magnetic film obtained in step (4) is subjected to annealing heat treatment.
[0048] Furthermore, in step (3), the deposition temperature of the Sm-Fe film is 250-700°C, preferably, the deposition temperature of the Sm-Fe film is 250-550°C.
[0049] In some specific embodiments, the annealing treatment is performed at a temperature of 700°C.
[0050] In some specific embodiments, the annealing heat treatment time is 30 to 60 minutes, preferably 45 to 60 minutes.
[0051] Furthermore, the annealing time of the Sm-Fe based permanent magnetic film at 700° C. is 15 to 60 minutes, preferably 45 to 60 minutes.
[0052] Specifically, when Sm-Fe in the Sm-Fe based permanent magnetic film x , when x = 1.9, SmFe annealed at 700℃ for 1h 1.9(500℃) / Ta(BA) film sample, the sample formed a pure phase SmFe2 polycrystalline film. The deposition of Ta capping layer can effectively prevent the volatilization of Sm. Under the appropriate composition ratio close to the SmFe2 phase, by adjusting the deposition temperature and annealing heat treatment time, a single-phase SmFe x Polycrystalline film. Higher deposition temperature and annealing temperature can improve SmFe x The purity of the phase is increased, its magnetostriction coefficient is improved, and the Sm-Fe based permanent magnetic film exhibits excellent magnetic anisotropy.
[0053] In summary, the Sm-Fe based permanent magnetic film prepared by the method of the present invention is a highly perpendicular anisotropic film, which exhibits a significantly higher coercive force in the perpendicular direction, reaching 2427Oe, exceeding the 650Oe of the film with a composition close to SmFe2 reported in the literature.
[0054] Furthermore, another aspect of an embodiment of the present invention also provides an application of the aforementioned Sm-Fe-based permanent magnetic film. Specifically, the Sm-Fe-based permanent magnetic film prepared by the present invention has excellent perpendicular anisotropy. The magnetic properties of this film in the vertical direction, such as magnetic permeability, magnetization intensity, etc., are generally better than those in the parallel direction, which makes them perform well in applications requiring perpendicular magnetic response, and have important application value in the applications of micro-electromechanical systems, microelectronic systems, magnetic recording materials and spin electronic devices.
[0055] In order to further illustrate the Sm-Fe-based permanent magnetic film prepared by the present invention, the present invention is further described below through the accompanying drawings and specific embodiments, but it does not mean to limit the scope of protection of the present invention. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. The experimental methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or under the conditions recommended by the manufacturer.
[0056] Comparative Example 1
[0057] The substrate used for preparing the Sm-Fe based permanent magnetic film in this comparative example is Si(100), on the surface of which is deposited a Ta buffer layer with a thickness of 50-100nm, on the surface of the Ta buffer layer is a Sm-Fe layer with a thickness of 950-1050nm, and on the surface of the Sm-Fe layer is a Ta capping layer with a thickness of 50-100nm. 0.5 The specific steps of permanent magnetic film are as follows:
[0058] (1) Cleaning a Si (100) substrate and then placing it into a sample chamber; bombarding the Si (100) substrate with ions by using radio frequency magnetron sputtering to obtain a bombarded Si (100) substrate and placing it into a high vacuum sample preparation chamber.
[0059] (2) Using Ta as the target, a Ta buffer layer with a thickness of 50-100 nm is deposited on the Si(100) substrate.
[0060] (3) Using Fe target and Sm target as target materials, a co-sputtering method is used to deposit a 950-1050 nm thick Sm-Fe layer on the Ta buffer layer obtained in step (2). 0.5 layer.
[0061] (4) Using Ta as the target, the Sm-Fe 0.5 A Ta capping layer with a thickness of 50-100 nm is deposited on the layer.
[0062] (5) The Sm-Fe obtained in step (4) 0.5 The base permanent magnetic film is annealed at 700°C for 60 minutes.
[0063] The SmFe of this comparative example was prepared using a dual-chamber magnetron sputtering system. 0.5 The specific conditions of permanent magnetic film are as follows:
[0064] The Si (100) substrate to be coated was ultrasonically cleaned with analytical grade acetone for 15 min / time for a total of 3 times. The cleaned Si (100) substrate was blown dry with nitrogen and sent to the injection chamber, where it was vacuumed to a pressure better than 4x10 -5 Pa. Then, the Si(100) substrate is ion bombarded to remove the impurities and oxide layer that may remain on the substrate surface, and the back vacuum is better than 4x10 -5 Pa, the sputtering gas is argon with a purity of 99.9995%, the gas flow rate is 32 sccm, a radio frequency sputtering power supply is used, the sputtering power is 40 W, and the sputtering is performed for 20 min at room temperature.
[0065] The Si(100) substrate was placed in a high vacuum chamber to prepare a thin film on the substrate surface. -6The target material to be sputtered is pre-sputtered at 1.50 Pa to remove possible impurities or oxide layers on the surface of the target material, so that the film to be deposited next is not doped with impurities. Pre-sputtering does not require sputtering power and time. Then, the Si (100) substrate is heated to 300 ° C, and argon gas with a purity of 99.9995% is used as the sputtering gas. Under the conditions of sputtering pressure of 0.8 Pa and gas flow rate of 32 sccm, a 99.99% Ta target is used as the target material to prepare a 50-100nm thick Ta buffer layer. The sputtering power of the Ta target is 120W, the sputtering rate is 11nm / min, and the deposition takes about 5 minutes.
[0066] The substrate with the deposited Ta buffer layer was heated to 500°C, and a Sm-Fe layer with a thickness of 950-1050 nm was sputtered using Fe and Sm targets as targets. The sputtering power of the Fe target was 16 W, the sputtering rate was 0.7 nm / min, the sputtering power of the Sm target was 100 W, the sputtering rate was 3.9 nm / min, and the co-deposition was about 3.6 hours. Here, the co-sputtering made the ratio of Sm:Fe 1:0.5.
[0067] The substrate temperature was lowered to 300°C, and a Ta cover layer with a thickness of 50-100 nm was prepared using a Ta target with a sputtering purity of 99.99%. The sputtering power of the Ta target was 120 W, the sputtering rate was 11 nm / min, and the deposition took about 5 minutes.
[0068] Under vacuum conditions, the Sm-Fe based permanent magnetic film samples prepared in this comparative example were subjected to annealing heat treatment. The permanent magnetic film samples were annealed at 700°C for 60 min. The hysteresis loops of the SmFe0.5 (500°C) / Ta (AA) film along the parallel ( / / ) and perpendicular (⊥) directions were measured using a vibrating magnetometer (e.g. Figure 3 ).Depend on Figure 3 It can be seen that the annealed SmFe0.5 (500 ° C) / Ta (BA) film does not show obvious magnetic anisotropy along the parallel and perpendicular directions of the sample. The reason for the lack of obvious magnetic anisotropy here may be that the ratio of SmFe is 1:0.5, which is not the best phase ratio, resulting in less SmFe phase or poor phase texture.
[0069] Comparative Example 2
[0070] The substrate used for preparing the Sm-Fe-based permanent magnetic film in this comparative example is Si (100), and a Ta buffer layer with a thickness of 50-100nm is deposited on its surface, a Sm-Fe layer with a thickness of 950-1050nm is deposited on the surface of the Ta buffer layer, and a Ta capping layer with a thickness of 50-100nm is deposited on the surface of the Sm-Fe layer. The specific steps for preparing the SmFe permanent magnetic film in this comparative example are as follows:
[0071] (1) Cleaning a Si (100) substrate and then placing it into a sample chamber; bombarding the Si (100) substrate with ions by using radio frequency magnetron sputtering to obtain a bombarded Si (100) substrate and placing it into a high vacuum sample preparation chamber.
[0072] (2) Using Ta as the target, a Ta buffer layer with a thickness of 50-100 nm is deposited on the Si(100) substrate.
[0073] (3) Using Fe target and Sm target as target materials, a Sm-Fe layer with a thickness of 950-1050 nm is deposited on the Ta buffer layer obtained in step (2) by a co-sputtering method.
[0074] (4) Using Ta as a target, a Ta capping layer with a thickness of 50-100 nm is deposited on the Sm-Fe layer obtained in step (3).
[0075] (5) The SmFe permanent magnetic film obtained in step (4) is annealed at 700°C for 60 minutes.
[0076] The specific conditions for preparing the SmFe permanent magnetic film of this comparative example using a dual-chamber magnetron sputtering system are as follows:
[0077] The Si (100) substrate to be coated was ultrasonically cleaned with analytical grade acetone for 15 min / time for a total of 3 times. The cleaned Si (100) substrate was blown dry with nitrogen and sent to the injection chamber, where it was vacuumed to a pressure better than 4x10 -5 Pa. Then, the Si(100) substrate is ion bombarded to remove the impurities and oxide layer that may remain on the substrate surface, and the back vacuum is better than 4x10 -5 Pa, the sputtering gas is argon with a purity of 99.9995%, the gas flow rate is 32 sccm, a radio frequency sputtering power supply is used, the sputtering power is 40 W, and the sputtering is performed for 20 min at room temperature.
[0078] The Si(100) substrate was placed in a high vacuum chamber to prepare a thin film on the substrate surface. -6 The target material to be sputtered is pre-sputtered at 1.50 Pa to remove the impurities or oxide layer that may exist on the surface of the target material, so that the film deposited next is not doped with impurities. The pre-sputtering does not require the sputtering power and time. Then the Si (100) substrate is heated to 300 ° C, and argon with a purity of 99.9995% is used as the sputtering gas, the sputtering pressure is 0.8 Pa, and the gas flow rate is 32 sccm; a 50nm thick Ta buffer layer is prepared with a 99.99% Ta target as the target material, the sputtering power of the Ta target is 120W, the sputtering rate is 11nm / min, and the deposition takes about 5 minutes.
[0079] The substrate with the deposited Ta buffer layer was heated to 500°C, and a Sm-Fe layer with a thickness of 950-1050 nm was sputtered using Fe and Sm targets as targets. The sputtering power of Fe was 31 W, the sputtering rate was 1.4 nm / min, the sputtering power of Sm target was 100 W, the sputtering rate was 3.9 nm / min, and the co-deposition was about 3.1 h. Here, the co-sputtering made the ratio of Sm:Fe 1:1.
[0080] The substrate temperature was lowered to 300° C., and a 50 nm thick Ta covering layer was prepared using a Ta target with a sputtering purity of 99.99%. The sputtering power of the Ta target was 120 W, the sputtering rate was 11 nm / min, and the deposition took about 5 minutes.
[0081] Under vacuum conditions, the Sm-Fe based permanent magnetic film sample prepared in this comparative example was annealed at 700°C for 60 min, and the hysteresis loops of the SmFe(500°C) / Ta(AA) film along the parallel ( / / ) and perpendicular (⊥) directions were measured using a vibrating magnetometer (e.g. Figure 4 ).Depend on Figure 4 It can be seen that when annealed at 700℃, the SmFe(500℃) / Ta(BA) film does not show obvious magnetic anisotropy along the parallel and perpendicular directions of the sample. The reason for not showing obvious magnetic anisotropy here may be that the ratio of SmFe is 1:1, which is not the optimal phase ratio, resulting in less SmFe phase or poor phase texture.
[0082] Example 1
[0083] The substrate used for preparing the Sm-Fe based permanent magnetic film in this embodiment is Si(100), on the surface of which is deposited a Ta buffer layer with a thickness of 50nm, on the surface of the Ta buffer layer is a Sm-Fe layer with a thickness of 1000nm, and on the surface of the Sm-Fe layer is a Ta capping layer with a thickness of 50nm. 1.9 The specific steps of permanent magnetic film are as follows:
[0084] (1) Cleaning a Si (100) substrate and then placing it into a sample chamber; using radio frequency magnetron sputtering to bombard the Si (100) substrate with ions, obtaining a bombarded Si (100) substrate and placing it into a high vacuum sample preparation chamber.
[0085] (2) Using Ta as the target, a 50 nm thick Ta buffer layer was deposited on the Si(100) substrate.
[0086] (3) Using Fe target and Sm target as target materials, a Sm-Fe layer with a thickness of 1000 nm is deposited on the Ta buffer layer obtained in step (2) by a co-sputtering method.
[0087] (4) Using Ta as a target, a 50 nm thick Ta capping layer is deposited on the SmFe1.9 layer obtained in step (3).
[0088] (5) The Sm-Fe based permanent magnetic film obtained in step (4) is subjected to annealing heat treatment at 700°C for 60 minutes.
[0089] The SmFe 1.9 The specific conditions of permanent magnetic film are as follows:
[0090] The Si (100) substrate to be coated was ultrasonically cleaned with analytical grade acetone for 15 min / time for a total of 3 times. The cleaned Si (100) substrate was blown dry with nitrogen and sent to the injection chamber, where it was vacuumed to a pressure better than 4x10 -5 Pa. Then, the Si(100) substrate is ion bombarded to remove the impurities and oxide layer that may remain on the substrate surface, and the back vacuum is better than 4x10 -5 Pa, the sputtering gas is argon with a purity of 99.9995%, the gas flow rate is 32 sccm, a radio frequency sputtering power supply is used, the sputtering power is 40 W, and the sputtering is performed for 20 min at room temperature.
[0091] The Si(100) substrate was placed in a high vacuum chamber to prepare a thin film on the substrate surface. -6 The target material to be sputtered is pre-sputtered at 1.50 Pa to remove the impurities or oxide layer that may exist on the surface of the target material, so that the film deposited next is not doped with impurities. The pre-sputtering does not require the sputtering power and time. Then the Si (100) substrate is heated to 300 ° C, and argon with a purity of 99.9995% is used as the sputtering gas, the sputtering pressure is 0.8 Pa, and the gas flow rate is 32 sccm; a 50nm thick Ta buffer layer is prepared with a 99.99% Ta target as the target material, the sputtering power of the Ta target is 120W, the sputtering rate is 11nm / min, and the deposition takes about 5 minutes.
[0092] The substrate with the deposited Ta buffer layer was heated to 500°C, and a Sm-Fe layer with a thickness of 950-1050 nm was sputtered using Fe and Sm targets as targets. The sputtering power of Fe was 61 W, the sputtering rate was 6.3 nm / min, the sputtering power of Sm target was 100 W, the sputtering rate was 3.9 nm / min, and the co-deposition was about 98 minutes. Here, the co-sputtering made the ratio of Sm:Fe 1:1.9.
[0093] The substrate temperature was lowered to 300°C, and a Ta cover layer with a thickness of 50-100 nm was prepared using a Ta target with a sputtering purity of 99.99%. The sputtering power of the Ta target was 120 W, the sputtering rate was 11 nm / min, and the deposition took about 5 minutes.
[0094] Under vacuum conditions, the SmFe prepared in this example 1.9 The permanent magnetic film samples were annealed at 700℃ for 60min and the SmFe 1.9 The hysteresis loops of (500℃) / Ta(BA) films along the parallel ( / / ) and perpendicular (⊥) directions (e.g. Figure 5 ).Depend on Figure 5 It can be seen that the SmFe1.9 (500 ° C) / Ta (AA) film annealed at 700 ° C for 60 minutes shows obvious differences in magnetic anisotropy along the parallel and perpendicular directions of the sample. Moreover, the saturation magnetization intensity in the direction perpendicular to the substrate is significantly higher than that in the parallel direction.
[0095] Furthermore, the inventors of this case also deposited SmFe on the basis of Example 1. x A series of experiments were conducted on the process of layer deposition, specifically: SmFex (x = 1.5-9) layer was deposited at 300 ° C, and then a 50-100nm Ta capping layer was deposited, and annealed at 700 ° C for 0.5h to obtain a Sm-Fe based permanent magnetic film. The XRD spectrum of the Sm-Fe based permanent magnetic film is shown in Figure 2a shown.
[0096] Furthermore, the inventors of this case also provided a method of preparing a Sm-Fe based permanent magnetic film by depositing a SmFe2 layer at a series of different temperatures (250°C to 700°C) and then depositing a 50-100nm Ta capping layer and annealing at 700°C for 0.5h. The XRD spectrum of the Sm-Fe based permanent magnetic film is shown in FIG. Figure 2b shown.
[0097] Furthermore, the inventors of this case also provided a method of depositing a 50-100nm Ta capping layer after depositing a SmFe2 layer at 300°C and annealing at 700°C for different times (15 minutes to 1 hour) to obtain a Sm-Fe-based permanent magnetic film. The XRD spectrum of the Sm-Fe-based permanent magnetic film is as follows: Figure 2c shown.
[0098] Furthermore, the inventors of this case also provide a method for depositing SmFe at 500°C. 1.9 A 50-100 nm Ta capping layer is deposited after the layer and annealed at 700° C. for 30 min-1 h to obtain an embodiment of a Sm-Fe-based permanent magnetic film. The XRD spectrum of the Sm-Fe-based permanent magnetic film is as follows: Figure 2d shown.
[0099] Example 2
[0100] The substrate used for preparing the Sm-Fe based permanent magnetic film in this embodiment is Si(100), on whose surface is deposited a Ta buffer layer with a thickness of 100nm, on the surface of the Ta buffer layer is a Sm-Fe layer with a thickness of 950nm, and on the surface of the Sm-Fe layer is a Ta capping layer with a thickness of 100nm. 1.9 The specific steps of permanent magnetic film are as follows:
[0101] (1) Cleaning a Si (100) substrate and then placing it into a sample chamber; using radio frequency magnetron sputtering to bombard the Si (100) substrate with ions, obtaining a bombarded Si (100) substrate and placing it into a high vacuum sample preparation chamber.
[0102] (2) Using Ta as the target, a 100 nm thick Ta buffer layer was deposited on the Si(100) substrate.
[0103] (3) Using Fe target and Sm target as target materials, a 950 μm thick Sm-Fe layer was deposited on the Ta buffer layer obtained in step (2) by co-sputtering. 1.9 layer.
[0104] (4) Using Ta as the target, the SmFe 1.9 A Ta capping layer with a thickness of 100 nm is deposited on the layer.
[0105] (5) The Sm-Fe based permanent magnetic film obtained in step (4) is subjected to annealing heat treatment at 700°C for 30 minutes.
[0106] The specific conditions for preparing the Sm-Fe based permanent magnetic film of this embodiment using a dual-chamber magnetron sputtering system are as follows:
[0107] The three Si (100) substrates to be coated were ultrasonically cleaned with analytical grade acetone for 15 min each time. The cleaned Si (100) substrates were blown dry with nitrogen and sent to the injection chamber, where they were evacuated to a vacuum better than 4x10 - 5 Pa. Then, the Si(100) substrate is ion bombarded to remove the impurities and oxide layer that may remain on the substrate surface, and the back vacuum is better than 4x10 -5 Pa, the sputtering gas is argon with a purity of 99.9995%, the gas flow rate is 32 sccm, a radio frequency sputtering power supply is used, the sputtering power is 40 W, and the sputtering is performed for 20 min at room temperature.
[0108] The Si(100) substrate was placed in a high vacuum chamber to prepare a thin film on the substrate surface. -6The target material to be sputtered is pre-sputtered at 1.50 Pa to remove the impurities or oxide layer that may exist on the surface of the target material, so that the film deposited next is not doped with impurities. The pre-sputtering does not require the sputtering power and time. Then the Si (100) substrate is heated to 300 ° C, and argon gas with a purity of 99.9995% is used as the sputtering gas. Under the conditions of sputtering pressure of 0.8 Pa and gas flow rate of 32 sccm, a 100nm thick Ta buffer layer is prepared with a 99.99% Ta target as the target material. The sputtering power of the Ta target is 120W, the sputtering rate is 11nm / min, and the deposition is about 5min.
[0109] The substrate with the deposited Ta buffer layer was kept at 300°C, and a 950nm thick Sm-Fe layer was sputtered using Fe target and Sm target as targets. The sputtering power of Fe was 61W, the sputtering rate was 6.3nm / min, the sputtering power of Sm target was 100W, the sputtering rate was 3.9nm / min, and the co-deposition time was about 98min.
[0110] The substrate temperature was maintained at 300° C., and a Ta cover layer with a thickness of 100 nm was prepared using a Ta target with a sputtering purity of 99.99%. The sputtering power of the Ta target was 120 W, the sputtering rate was 11 nm / min, and the deposition time was about 5 minutes.
[0111] The substrate with the deposited Ta buffer layer was heated to 550°C, and a 950nm thick Sm-Fe layer was sputtered using Fe and Sm targets as targets. The sputtering power of Fe was 61W, the sputtering rate was 6.3nm / min, the sputtering power of Sm target was 100W, the sputtering rate was 3.9nm / min, and the co-deposition was about 98min. Here, the co-sputtering made the ratio of Sm:Fe 1:1.9.
[0112] The substrate temperature was lowered to 300° C., and a Ta cover layer with a thickness of 100 nm was prepared using a Ta target with a sputtering purity of 99.99%. The sputtering power of the Ta target was 120 W, the sputtering rate was 11 nm / min, and the deposition took about 5 minutes.
[0113] The substrate was subjected to annealing heat treatment at 700°C for 30 minutes.
[0114] Under vacuum conditions, the SmFe prepared in this example 1.9 The permanent magnetic film sample was annealed at 700℃ and the magnetostrictive properties of the film material were measured using the SmFe 1.9 Magnetostriction coefficient diagram of (300℃ / 550℃) / Ta(BA) film after annealing at 700℃ for different times (see Figure 6 ).Depend on Figure 6 It can be seen that SmFe 1.9Magnetostriction coefficient diagram of (T) / Ta(BA) films with 1:2 phase as the main phase prepared at different deposition temperatures and annealing times. At the same deposition temperature, the longer the annealing time, the larger the magnetostriction coefficient (λ) of the Sm-Fe film. This is because the longer the annealing time, the larger the grain size, indicating that long annealing treatment helps to improve the magnetostriction coefficient of the film. In addition, the magnetostriction coefficient of the sample deposited at 550℃ and annealed at 700℃ for 30min is higher than that of the sample deposited at 300℃ and annealed at 700℃ for 45min. This is because the higher temperature deposition and heat treatment result in a higher purity of the SmFe2 phase.
[0115] Example 3
[0116] The substrate used for preparing the Sm-Fe based permanent magnetic film in this embodiment is Si(100), on whose surface is deposited a Ta buffer layer with a thickness of 100nm, on the surface of the Ta buffer layer is a Sm-Fe layer with a thickness of 1050nm, and on the surface of the Sm-Fe layer is a Ta capping layer with a thickness of 100nm. 1.9 The specific steps of permanent magnetic film are as follows:
[0117] (1) Cleaning a Si (100) substrate and then placing it into a sample chamber; using radio frequency magnetron sputtering to bombard the Si (100) substrate with ions, obtaining a bombarded Si (100) substrate and placing it into a high vacuum sample preparation chamber.
[0118] (2) Using Ta as the target, a 100 μm thick Ta buffer layer was deposited on the Si (100) substrate.
[0119] (3) Using Fe target and Sm target as target materials, a co-sputtering method is used to deposit a 1050 nm thick Sm-Fe layer on the Ta buffer layer obtained in step (2). 1.9 layer.
[0120] (4) Using Ta as the target, the SmFe 1.9 A Ta capping layer with a thickness of 100 nm is deposited on the layer.
[0121] (5) The Sm-Fe based permanent magnetic film obtained in step (4) is subjected to annealing heat treatment at 700°C for 45 minutes.
[0122] The specific conditions for preparing the Sm-Fe based permanent magnetic film of this embodiment using a dual-chamber magnetron sputtering system are as follows:
[0123] The three Si (100) substrates to be coated were ultrasonically cleaned with analytical grade acetone for 15 min each time. The cleaned Si (100) substrates were blown dry with nitrogen and sent to the injection chamber, where they were evacuated to a vacuum better than 4x10 - 5Pa. Then, the Si(100) substrate is ion bombarded to remove the impurities and oxide layer that may remain on the substrate surface, and the back vacuum is better than 4x10 -5 Pa, the sputtering gas is argon with a purity of 99.9995%, the gas flow rate is 32 sccm, a radio frequency sputtering power supply is used, the sputtering power is 40 W, and the sputtering is performed for 20 min at room temperature.
[0124] The Si(100) substrate was placed in a high vacuum chamber to prepare a thin film on the substrate surface. -6 The target material to be sputtered is pre-sputtered at 1.50 Pa to remove possible impurities or oxide layers on the surface of the target material, so that the film to be deposited next is not doped with impurities. Pre-sputtering does not require sputtering power and time. Then, the Si (100) substrate is heated to 300 ° C, and argon gas with a purity of 99.9995% is used as the sputtering gas. Under the conditions of sputtering pressure of 0.8 Pa and gas flow rate of 32 sccm, a 50nm thick Ta buffer layer is prepared with a 99.99% Ta target as the target material. The sputtering power of the Ta target is 120W, the sputtering rate is 11nm / min, and the deposition is about 5min.
[0125] The substrate with the deposited Ta buffer layer was kept at 300°C, and a 1050nm thick Sm-Fe layer was sputtered using Fe and Sm targets as targets. The sputtering power of Fe was 61W, the sputtering rate was 6.3nm / min, the sputtering power of Sm target was 100W, the sputtering rate was 3.9nm / min, and the co-deposition was about 98min. Here, the co-sputtering made the ratio of Sm:Fe 1:1.9.
[0126] The substrate temperature was maintained at 300° C., and a Ta cover layer with a thickness of 100 nm was prepared using a Ta target with a sputtering purity of 99.99%. The sputtering power of the Ta target was 120 W, the sputtering rate was 11 nm / min, and the deposition time was about 5 minutes.
[0127] The substrate was subjected to annealing heat treatment at 700°C for 45 minutes.
[0128] Under vacuum conditions, the SmFe prepared in this example 1.9 The permanent magnetic film sample was annealed at 700℃ and the magnetostrictive properties of the film material were measured using the SmFe 1.9 Magnetostriction coefficient diagram of (300℃ / 300℃) / Ta(BA) film after annealing at 700℃ for different time (see Figure 6 ).Depend on Figure 6 It can be seen that SmFe 1.9Magnetostriction coefficient diagram of (T) / Ta(BA) films with 1:2 phase as the main phase prepared at different deposition temperatures and annealing times. At the same deposition temperature, the longer the annealing time, the larger the magnetostriction coefficient (λ) of the Sm-Fe film. This is because the longer the annealing time, the larger the grain size, indicating that long annealing treatment helps to improve the magnetostriction coefficient of the film. In addition, the magnetostriction coefficient of the sample deposited at 550℃ and annealed at 700℃ for 30min is higher than that of the sample deposited at 300℃ and annealed at 700℃ for 45min. This is because the higher temperature deposition and heat treatment result in a higher purity of the SmFe2 phase.
[0129] Example 4
[0130] The substrate used for preparing the Sm-Fe based permanent magnetic film in this embodiment is Si(100), on the surface of which is deposited a Ta buffer layer with a thickness of 50nm, on the surface of the Ta buffer layer is a Sm-Fe layer with a thickness of 1000nm, and on the surface of the Sm-Fe layer is a Ta capping layer with a thickness of 50nm. 1.9 The specific steps of permanent magnetic film are as follows:
[0131] (1) Cleaning a Si (100) substrate and then placing it into a sample chamber; using radio frequency magnetron sputtering to bombard the Si (100) substrate with ions, obtaining a bombarded Si (100) substrate and placing it into a high vacuum sample preparation chamber.
[0132] (2) Using Ta as the target, a 50 nm thick Ta buffer layer was deposited on the Si(100) substrate.
[0133] (3) Using Fe target and Sm target as target materials, a 1000 nm thick Sm-Fe layer is deposited on the Ta buffer layer obtained in step (2) by co-sputtering. 1.9 layer.
[0134] (4) Using Ta as the target, the SmFe 1.9 A 50 nm thick Ta capping layer is deposited on the layer.
[0135] (5) The Sm-Fe based permanent magnetic film obtained in step (4) is subjected to annealing heat treatment at 700°C for 30 minutes.
[0136] The specific conditions for preparing the Sm-Fe based permanent magnetic film of this embodiment using a dual-chamber magnetron sputtering system are as follows:
[0137] The three Si (100) substrates to be coated were ultrasonically cleaned with analytical grade acetone for 15 min each time. The cleaned Si (100) substrates were blown dry with nitrogen and sent to the injection chamber, where they were evacuated to a vacuum better than 4x10 - 5Pa. Then, the Si(100) substrate is ion bombarded to remove the impurities and oxide layer that may remain on the substrate surface, and the back vacuum is better than 4x10 -5 Pa, the sputtering gas is argon with a purity of 99.9995%, the gas flow rate is 32 sccm, a radio frequency sputtering power supply is used, the sputtering power is 40 W, and the sputtering is performed for 20 min at room temperature.
[0138] The Si(100) substrate was placed in a high vacuum chamber to prepare a thin film on the substrate surface. -6 The target material to be sputtered is pre-sputtered at 1.50 Pa to remove possible impurities or oxide layers on the surface of the target material, so that the film to be deposited next is not doped with impurities. Pre-sputtering does not require sputtering power and time. Then, the Si (100) substrate is heated to 300 ° C, and argon gas with a purity of 99.9995% is used as the sputtering gas. Under the conditions of sputtering pressure of 0.8 Pa and gas flow rate of 32 sccm, a 50nm thick Ta buffer layer is prepared with a 99.99% Ta target as the target material. The sputtering power of the Ta target is 120W, the sputtering rate is 11nm / min, and the deposition is about 5min.
[0139] The substrate with the deposited Ta buffer layer was kept at 300°C, and a 1000nm thick Sm-Fe layer was sputtered using Fe and Sm targets as targets. The sputtering power of Fe was 61W, the sputtering rate was 6.3nm / min, the sputtering power of Sm target was 100W, the sputtering rate was 3.9nm / min, and the co-deposition was about 98min. Here, the co-sputtering made the ratio of Sm:Fe 1:1.9.
[0140] The substrate temperature was maintained at 300° C., and a Ta cover layer with a thickness of 100 nm was prepared using a Ta target with a sputtering purity of 99.99%. The sputtering power of the Ta target was 120 W, the sputtering rate was 11 nm / min, and the deposition time was about 5 minutes.
[0141] The substrate temperature of the deposited Ta buffer layer was maintained at 300°C, and a 1000nm thick Sm-Fe layer was sputtered using Fe target and Sm target as targets. The sputtering power of Fe was 61W, the sputtering rate was 6.3nm / min, the sputtering power of Sm target was 100W, the sputtering rate was 3.9nm / min, and the co-deposition was about 98min.
[0142] The substrate temperature was maintained at 300° C., and a Ta cover layer with a thickness of 100 nm was prepared using a Ta target with a sputtering purity of 99.99%. The sputtering power of the Ta target was 120 W, the sputtering rate was 11 nm / min, and the deposition took about 5 minutes.
[0143] The substrate was subjected to annealing heat treatment at 700°C for 60 minutes.
[0144] Under vacuum conditions, the SmFe prepared in this example 1.9 The permanent magnetic film sample was annealed at 700℃ and the magnetostrictive properties of the film material were measured using the SmFe 1.9 Magnetostriction coefficient diagram of (300℃ / 300℃) / Ta(BA) film after annealing at 700℃ for different time (see Figure 6 ).Depend on Figure 6 It can be seen that SmFe 1.9 Magnetostriction coefficient diagram of (T) / Ta(BA) films with 1:2 phase as the main phase prepared at different deposition temperatures and annealing times. At the same deposition temperature, the longer the annealing time, the larger the magnetostriction coefficient (λ) of the Sm-Fe film. This is because the longer the annealing time, the larger the grain size, indicating that long-term annealing treatment helps to improve the magnetostriction coefficient of the film. In addition, the magnetostriction coefficient of the sample deposited at 550℃ and annealed at 700℃ for 30min is higher than that of the sample deposited at 300℃ and annealed at 700℃ for 45min. This is because the higher temperature deposition and heat treatment make the SmFe2 phase purer. The magnetostriction coefficient of the sample deposited at 300℃ and annealed at 700℃ for 60min reaches the maximum, due to Figure 2b It can be seen that 250-350℃ is the ideal phase formation temperature of SmFe2. On this basis, extending the annealing heat treatment time is more effective.
[0145] In addition, the inventors of this case also conducted experiments with other raw materials and conditions listed in this specification in accordance with the above embodiments, and obtained similar results.
[0146] It should be noted that the above is only a preferred embodiment of the present application and is not intended to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A Sm-Fe based permanent magnetic film, characterized in that: The invention comprises a Ta buffer layer, a Sm-Fe layer and a Ta cap layer which are sequentially stacked in the thickness direction of the substrate, wherein the Sm-Fe layer has a magnetic perpendicular anisotropy, and the Sm-Fe layer comprises pure SmFe x Phase polycrystalline film, x = 1.8N2.
2. The Sm-Fe based permanent magnetic film according to claim 1, characterized in that: The Sm-Fe layer comprises pure SmFe 1.9 Phase polycrystalline thin film; the thickness of the Sm-Fe layer is 950 to 1050 nm.
3. The Sm-Fe based permanent magnetic film according to claim 1, characterized in that: The substrate includes at least any one of a Si substrate, a Si / SiO2 substrate, and an alumina substrate. Preferably, the substrate is a Si(100) substrate.
4. The Sm-Fe based permanent magnetic film according to claim 1, characterized in that: The thickness of the Ta buffer layer is 50-100 nm; and / or the thickness of the Ta capping layer is 50-100 nm; and / or the thickness of the Sm-Fe-based permanent magnetic film is 1050-1250 nm.
5. The method for preparing the Sm-Fe based permanent magnetic film according to any one of claims 1 to 4, characterized in that: include: A Ta buffer layer, a Sm-Fe layer and a Ta capping layer are sequentially deposited on a substrate by magnetron sputtering technology, and then the obtained composite film is subjected to annealing heat treatment to obtain a Sm-Fe-based permanent magnetic film.
6. The preparation method according to claim 5, characterized in that: include: The magnetron sputtering technology is adopted, with an inert gas as the sputtering gas and a Ta target as the target material, to sputter and deposit a Ta buffer layer on the surface of the substrate; wherein the pressure of the inert gas used is 0.8-3Pa, the sputtering power is 50-120W, the sputtering time is 5-10min, and the deposition temperature is 250-350°C.
7. The preparation method according to claim 5, characterized in that: include: The magnetron sputtering technology is adopted, inert gas is used as sputtering gas, Fe target and Sm target are used as target materials, and a co-sputtering method is used to sputter and deposit a Sm-Fe layer on the surface of the Ta buffer layer; wherein the pressure of the inert gas used is 0.8-3 Pa, the sputtering power is 10-150 W, the sputtering time is 10-250 min, and the deposition temperature is 250-700 ° C, preferably 250-550 ° C.
8. The preparation method according to claim 5, characterized in that: include: Magnetron sputtering technology is adopted, with inert gas as sputtering gas and Ta target as target material, to sputter and deposit a Ta covering layer on the surface of the Sm-Fe layer; wherein the pressure of the inert gas used is 0.8-3Pa, the sputtering power is 50-120W, the sputtering time is 3-60min, and the deposition temperature is 250-350°C.
9. The preparation method according to any one of claims 6, 7 and 8, characterized in that: The temperature of the annealing heat treatment is 700°C, and the time of the annealing heat treatment is 30 to 60 minutes, preferably 45 to 60 minutes; The inert gas includes argon; The preparation method also includes: before depositing the Ta buffer layer on the substrate, using magnetron sputtering technology, using inert gas as sputtering gas, to bombard the substrate surface with ions; wherein the pressure of the inert gas used is 1-5 Pa, the sputtering power is 20-60 W, and the sputtering time is 10-40 min.
10. Use of the Sm-Fe based permanent magnetic film according to any one of claims 1 to 4 in microelectronic systems, microelectromechanical systems, magnetic recording materials or spintronic devices.
Citation Information
Patent Citations
Magnetoelectric coupling heterogeneous structure as well as preparation method and application thereof
CN106449971A
Nd-Fe-B based permanent magnet film and preparation method and application thereof
CN116580910A
Super-magnetostrictive thin-film element and method of manufacturing the same
JP2009231349A
Multilayers with perpendicular magnetic anisotropy
KR101519767B1